As políticas educacionais gaúchas no governo Eduardo Leite (2019-2021): uma manifestação singular da subsunção do trabalho pedagógico ao capital - Fuchs, Marcius Minervini (2022)
Capitalism is currently experiencing a structural crisis, which puts chronic unemployment in vogue, the destruction of productive forces, the impossibility of equality between human beings and the confrontation of interests between the State and global capital. This reality manifests itself in all social spheres, including education, where educational policies emanate from the State. In Rio Grande do Sul, with the beginning of the government of Eduardo Leite, of the Brazilian Social Democracy Party (PSDB), the approved reforms, in addition to the pandemic context of covid-19, directly influenced the pedagogical work. With that in mind, the following problematization was elaborated: in the current context, what do the educational public policies of the Eduardo Leite government aim for regarding the conditions and functions of pedagogical work in the state network of Basic Education in Rio Grande do Sul? As a hypothesis, it was assumed that the educational policies of the Government of the State of Rio Grande do Sul can adapt the pedagogical work to the systemic demands, with the intensification of the precariousness of the working conditions, aiming at characteristics of polyvalence, lyophilization, increase of dead work, flexibility and work intensification. In addition, regarding the functions of the pedagogical work, it was assumed that such policies contributed to the formation of a workforce with characteristics necessary for the current context of the Industry 4.0 world of work. To carry out the proposed investigation, bibliographic research and document analysis were used, based on Historical-Dialectic Materialism as a theoreticalmethodological contribution. The data produced made it possible to formulate that, starting from the relation of subsumption of pedagogical work to capital, Leite's educational policies manifest, in their uniqueness, the objectification of adaptability to systemic demands, enabling the precariousness of working conditions and greater difficulty in access to rights and benefits historically conquered by the teaching category. And, as for functions, it aims at training a workforce with characteristics of uberized work, such as versatility, lyophilization, flexibility and work intensification.